Constructing and optimizing ecological network at county and town Scale: The case of Anji County, China - Wenbin Nie (Elsevier, 2021)
Rapid urbanization has led to increasingly fragmented urban habitat patches, and the biodiversity within these patches and in their surrounding areas is severely threatened. This ecological problem is spreading from cities to counties dominated by villages and towns, and is especially prevalent in economically developed areas. Constructing a reasonable ecological network is an effective way to balance the contradiction between regional development and ecological protection. Taking Anji County of the Zhejiang Province, China as an example, this study first identified ecological sources based on morphological spatial pattern analysis (MSPA) and connectivity analysis, and then extracted and constructed ecological networks by using a minimum cumulative resistance (MCR) model and network analysis. Finally, the results were optimized by adding additional ecological sources and setting stepping stones. The priority of the corridor is determined by the gravity model, and the analysis of the ecological networks in this study drills down to the town scale. The results show that the initially constructed ecological network includes 10 ecological sources and 22 ecological corridors, of which six are important ecological corridors that need priority construction. However, the ecological networks were less distributed in the central and northern regions, so four supplementary ecological sources and two stepping stones were added to optimize the ecological network. The connectivity of the optimized ecological network improved, and the values of α (the closure), β (line-point rate) and γ (network connectivity) increased by 4.6%, 10.45% and 2.18%, respectively. In addition, there were obvious differences in the area and land use types of ecological networks among towns, so it is necessary to formulate targeted construction strategies. Through an in-depth analysis from county to town, this study makes the construction and management of ecological networks more operable for country administration, and provides reference for the balance of ecological protection and regional development at the county level.